2019
DOI: 10.3233/jnd-190386
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden and Related Factors Among Caregivers of Patients with Myotonic Dystrophy Type 1

Abstract: Background: Multi-systemic symptoms of varying severity in myotonic dystrophy type 1 (DM1) may pose difficulties in caregiving. However, the factors which affect their care burden are yet to be sufficiently understood. Objective: We investigated care burden and its correlates among caregivers of patients with DM1. Methods: General demographic information was obtained from patients with DM1, as well as Barthel index (ADL), body mass index, and genetic information. Patients completed SF-36v2 (health-related qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Moreover, white matter tract mean diffusivity in the superior longitudinal fasciculus and cingulum has been associated with an increased score on the Epworth Sleepiness Scale (4). The prevalent symptom of hypersomnolence causes major morbidity in DM1 (16,45,(78)(79)(80)(81). Although relatively FIGURE 1 | Disease duration as a predictor of clinical measures in DM1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, white matter tract mean diffusivity in the superior longitudinal fasciculus and cingulum has been associated with an increased score on the Epworth Sleepiness Scale (4). The prevalent symptom of hypersomnolence causes major morbidity in DM1 (16,45,(78)(79)(80)(81). Although relatively FIGURE 1 | Disease duration as a predictor of clinical measures in DM1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, white matter tract mean diffusivity in the superior longitudinal fasciculus and cingulum has been associated with an increased score on the Epworth Sleepiness Scale ( 4 ). The prevalent symptom of hypersomnolence causes major morbidity in DM1 ( 16 , 45 , 78 81 ). Although relatively crudely tracked by self-report in this current study, this feature can also be evaluated by quantitative assessment such as EEG from polysomnography, which could be used in future studies or clinical trials ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in various conditions have reported a significant impact on caregivers' mental health, with a high prevalence of anxiety and depression symptoms [136,137]. These are often related to: the amount of time spent providing care [136,138]; the severity of the condition, as well as the emotional health of the patient [139,140]; isolation due to care commitments [138,141]; and physical difficulties such as the introduction of a wheelchair [142].…”
Section: Burden On Caregiversmentioning
confidence: 99%
“…People affected by NMD diseases may have limited functional capacity to perform certain daily activities and often require caregiver assistance. This adds to the complexity of studying the NMD population given that patients may rely significantly on caregivers for relevant care-related decisions 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%